2013
DOI: 10.1007/978-3-642-40164-0_11
|View full text |Cite
|
Sign up to set email alerts
|

An O *(1.84 k ) Parameterized Algorithm for the Multiterminal Cut Problem

Abstract: We study the multiterminal cut problem, which, given an n-vertex graph whose edges are integer-weighted and a set of terminals, asks for a partition of the vertex set such that each terminal is in a distinct part, and the total weight of crossing edges is at most k. Our weapons shall be two classical results known for decades: maximum volume minimum (s,t)-cuts by [Ford and Fulkerson, Flows in Networks, 1962] and isolating cuts by [Dahlhaus et al., SIAM J. Comp. 23(4):864-894, 1994]. We sharpen these old weap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(41 citation statements)
references
References 23 publications
1
40
0
Order By: Relevance
“…Lemma 1 [7] If an edge e = (u, v) ∈ G is guaranteed not to be in at least one multiterminal cut C(G) (i.e. P u = P v ), we can contract e and W(G/e) = W(G).…”
Section: Kernelizationmentioning
confidence: 99%
See 2 more Smart Citations
“…Lemma 1 [7] If an edge e = (u, v) ∈ G is guaranteed not to be in at least one multiterminal cut C(G) (i.e. P u = P v ), we can contract e and W(G/e) = W(G).…”
Section: Kernelizationmentioning
confidence: 99%
“…Lemma 2 [7] If an edge e = (u, v) ∈ E is guaranteed to be in a minimum multiterminal cut, i.e. there is a minimum multiterminal cut C(G) in which P u = P v , we can delete e from G and C(G − e) is still a valid minimum multiterminal cut.…”
Section: Proofmentioning
confidence: 99%
See 1 more Smart Citation
“…1.1. 3 Step III: Reducing k-Cut to Laminar k-cut We now reduce the general k-Cut problem to Laminar k-cut. This reduction is again based on observations about the graph structure in cases where the iterative greedy algorithms do not get a (2 − ε)-approximation.…”
Section: 12mentioning
confidence: 99%
“…Together with its close relative Odd Cycle Transversal (OCT), where one deletes vertices instead of edges, Edge Bipartization was one of the first problems shown to admit a fixed-parameter (FPT) algorithm using the technique of iterative compression. In a breakthrough paper [28] that introduces this methodology, Reed et al showed how to solve OCT in time O(3 k · kmn) 1 . In fact, this was the first FPT algorithm for OCT.…”
Section: Introductionmentioning
confidence: 99%